COGNITIVE AND SOCIOEMOTIONAL FUNCTIONING AT 4½ YEARS IN CHILDREN BORN TO MOTHERS WHO HAVE RECEIVED TREATMENT FOR SUBSTANCE‐ABUSE PROBLEMS WHILE PREGNANT. Issue 5 (7th August 2018) - Haabrekke, Kristin; Siqveland, Torill; Nygaaard, Egil; Bjornebekk, Astrid; Slinning, Kari; Wentzel‐Larsen, Tore; Walhovd, Kristine B.; Smith, Lars; Moe, Vibeke
ABSTRACT: Cognitive and socioemotional functioning at 4½ years of age were examined in children born to mothers with substance‐abuse problems ( n = 22) recruited from residential treatment institutions while pregnant, and then compared to children born to mothers with mental health problems ( n = 18) and children from a low‐risk group ( n = 26). No significant group differences in cognitive functioning were found, but the children born to mothers with substance‐abuse problems showed more caregiver‐reported socioemotional problems than did the low‐risk children, like the children born to mothers with mental health problems. Birth weight had an effect on internalizing problems at 4½ years and mediated the relation between group and socioemotional problems, although not when controlling for caregiver education, single parenthood, and anxiety and depression. At 4½ years, 7 children born to mothers with substance‐abuse problems were placed in foster care. These children had lower birth weight and higher caregiver‐rated internalizing problems. In addition to emphasizing the importance of the quality of the prenatal environment, this study suggests that families with previous substance abuse are in need of long‐term follow‐up to address socioemotional problems and enhance further positive child cognitive development. The foster‐placed children may be in particular need of long‐term follow‐up.